Further delineation of auriculocondylar syndrome based on 14 novel cases and reassessment of 25 published cases. Issue 5 (7th March 2022) - Vegas, Nancy; Demir, Zeynep; Gordon, Christopher T.; Breton, Sylvain; Romanelli Tavares, Vanessa L.; Moisset, Hugo; Zechi‐Ceide, Roseli; Kokitsu‐Nakata, Nancy M.; Kido, Yasuhiro; Marlin, Sandrine; Gherbi Halem, Souad; Meerschaut, Ilse; et al.
Abstract: Auriculocondylar syndrome (ACS) is a rare craniofacial disorder characterized by mandibular hypoplasia and an auricular defect at the junction between the lobe and helix, known as a "Question Mark Ear" (QME). Several additional features, originating from the first and second branchial arches and other tissues, have also been reported. ACS is genetically heterogeneous with autosomal dominant and recessive modes of inheritance. The mutations identified to date are presumed to dysregulate the endothelin 1 signaling pathway. Here we describe 14 novel cases and reassess 25 published cases of ACS through a questionnaire for systematic data collection. All patients harbor mutation(s) in PLCB4, GNAI3, or EDN1 . This series of patients contributes to the characterization of additional features occasionally associated with ACS such as respiratory, costal, neurodevelopmental, and genital anomalies, and provides management and monitoring recommendations. Abstract : We report clinical and molecular data for a large series of patients with the rare craniofacial disorder auriculocondylar syndrome (ACS), and we highlight how extra‐craniofacial features can occasionally be associated with ACS.